2022
DOI: 10.1097/ruq.0000000000000632
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Evidence of Testicular Damage in Severe Acute Respiratory Syndrome Coronavirus 2 Infection: A Sonoelastography's Potential Role

Abstract: This preliminary study aimed to evaluate the possible damage to the male reproductive system that the severe acute respiratory syndrome coronavirus 2 virus causes by quantitatively measuring and comparing the tissue stiffness of the testis and epididymis with acoustic radiation force impulse sonoelastography in patients who have COVID-19 with a healthy control group. This prospective study was conducted between February and July 2021 with 65 cases. We used sonoelastography to evaluate male patients 18 years or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…and it has been reported that SW-USE has already been used in the diagnosis of other diseases associated with the COVID-19 pandemic [42].…”
Section: Discussionmentioning
confidence: 99%
“…and it has been reported that SW-USE has already been used in the diagnosis of other diseases associated with the COVID-19 pandemic [42].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease, renal fibrosis, renal tumors, diabetic renal disease, and urogenital, pancreatic, prostate, and spleen diseases can also be evaluated with USE techniques [ 11 , 12 , 37 40 ]. In a recent study, Fusco et al claimed that USE could be used in the differential diagnosis of COVID-19 pneumoniae [ 41 ], and it has been reported that SW-USE has already been used in the diagnosis of other diseases associated with the COVID-19 pandemic [ 42 ].…”
Section: Discussionmentioning
confidence: 99%